Evaluation of wound healing activity of the crude extract and solvent fractions of Vahl (Polygonaceae) leaves in mice - Abel Andualem; Kefyalew Ayalew Getahun; Bahiru Tenaw Goshu; Yaschilal Muche Belayneh (Scars, Burns & Healing)
Background In Ethiopian traditional medicine, Rumex nervosus Vahl leaves are used to treat wounds. However, despite traditional claims and supportive in vitro findings, no scientific study has been conducted to evaluate the in vivo wound healing activity of R. nervosus Vahl leaves. Aim of the study To evaluate the wound healing activity of crude extract of the leaves of R. nervosus Vahl and its solvent fractions in mice. Methods R. nervosus Vahl leaves were extracted with 80% methanol, and then the crude extract was fractionated using ethyl acetate, chloroform, and water. Ointments at 5% and 10% strengths were formulated from the crude extract and its fractions. The healing activity of the crude extract was evaluated using linear incision, circular excision, and burn wound models in mice. Additionally, the activity of solvent fractions was assessed using circular excision wounds in mice. Results Treatment of wounds with ointments containing 5% and 10% crude extract showed significantly increased wound contraction rate, shorter epithelialization period, and higher skin-breaking strength (P < 0.05) compared with the negative control. Both 5% and 10% formulations of the aqueous and ethyl acetate fractions significantly increased wound contraction and decreased the period of epithelialization in the excision wound model (p < 0.05), however, the chloroform fraction showed no significant wound healing effect compared with the negative control. Conclusion The 80% methanol crude extract as well as the aqueous and ethyl acetate fractions of R. nervosus Vahl leaves possess wound healing activity as evidenced by improved wound contraction rate and tensile strength and decreased epithelialization period.